2018
DOI: 10.1111/ejh.13185
|View full text |Cite
|
Sign up to set email alerts
|

Comparative risk of major bleeding with rivaroxaban and warfarin: Population‐based cohort study of unprovoked venous thromboembolism

Abstract: Objectives To assess the association between rivaroxaban and warfarin and major bleeding risk in unprovoked venous thromboembolism (VTE) patients. Methods Using US MarketScan claims from 1/2012‐12/2016, we identified patients who had ≥1 primary hospitalization/emergency department visit diagnosis code for an unprovoked VTE, newly initiated on rivaroxaban or warfarin within 30 days after the VTE and ≥12 months of insurance coverage prior to the VTE. Differences in baseline covariates were adjusted using inverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…Some reports suggested that there was no difference in bleeding in clinical practice, 24, 25 whereas others reported that the DOACs group had reduced bleeding. 26, 27 The target PT-INR in the present study was 1.5-2.5, which may be one of the reasons for the lack of difference in bleeding incidence between the groups. DOACs have been reported to improve quality of life 28 and shorten the length of hospital stay; 29 this therapy also does not require frequent dose adjustments like warfarin.…”
Section: Discussionmentioning
confidence: 51%
“…Some reports suggested that there was no difference in bleeding in clinical practice, 24, 25 whereas others reported that the DOACs group had reduced bleeding. 26, 27 The target PT-INR in the present study was 1.5-2.5, which may be one of the reasons for the lack of difference in bleeding incidence between the groups. DOACs have been reported to improve quality of life 28 and shorten the length of hospital stay; 29 this therapy also does not require frequent dose adjustments like warfarin.…”
Section: Discussionmentioning
confidence: 51%
“…No evidence of visceral organ hemorrhage has been observed in LV patients treated with rivaroxaban. Comparison of the bleeding risks of rivaroxaban and warfarin showed that rivaroxaban had reduced risks of overall, gastrointestinal, and intracranial major bleeding in patients with unprovoked venous thromboembolism 22 . A few cases of rivaroxaban‐induced hepatotoxicity have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of the bleeding risks of rivaroxaban and warfarin showed that rivaroxaban had reduced risks of overall, gastrointestinal, and intracranial major bleeding in patients with unprovoked venous thromboembolism. 22 A few cases of rivaroxaban-induced hepatotoxicity have been documented. Liver damage was classified as hepatocellular, cholestatic, or mixed; hepatocellular was the major type.…”
Section: Discussionmentioning
confidence: 99%
“…As the second publication concerned a subgroup of 5004 patients with unprovoked venous thromboembolism within the study reported in the first publication (including 12,318 patients), only this larger study was retained [18]. Five studies conducted on the same American database (US Truven Market scan) were found [20][21][22][23][24]. Three studies [20][21][22] were excluded because they evaluated the same patients as two other larger studies [23,24], and more than half of their enrollment periods overlapped with those of the other studies.…”
Section: Study Identificationmentioning
confidence: 99%
“…Five studies conducted on the same American database (US Truven Market scan) were found [20][21][22][23][24]. Three studies [20][21][22] were excluded because they evaluated the same patients as two other larger studies [23,24], and more than half of their enrollment periods overlapped with those of the other studies. Finally, 26 studies (totalling 276,092 patients) were included : 6 RCTs [25-30], 4 prospective cohort studies [31][32][33][34], 12 studies using living databases (2 using living clinical databases [35][36] and 10 using living health administrative databases [18,23,24,[37][38][39][40][41][42][43]), and 4 retrospective cohort studies [44][45][46][47].…”
Section: Study Identificationmentioning
confidence: 99%